2016
DOI: 10.1002/pssr.201510423
|View full text |Cite
|
Sign up to set email alerts
|

Simple solar cells of 3.5% efficiency with antimony sulfide‐selenide thin films

Abstract: Thin films of antimony sulfide‐selenide solid solutions (Sb2Sx Se3–x) were prepared by chemical bath deposition and thermal evaporation to constitute solar cells of a transparent conductive oxide (FTO)/CdS/Sb2Sx Se3–x/C–Ag. The cell parameters vary depending on the sulfide‐selenide composition in the films. The best solar cell efficiency of 3.6% was obtained with a solid solution Sb2S1.5Se1.5 prepared by thermal evaporation of the precipitate for which the open circuit voltage is 0.52 V and short circuit curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…However, we reported that the chemical precipitate is rich in elemental selenium, and hence, the composition is shifted toward Sb 2 S 1.5 Se 1.5 . 26 If E g of bulk Sb 2 S 3 (1.88 eV) and Sb 2 Se 3 (1.1 eV) and proportional variation of E g are valid for this solid solution, its value for this thin film would be 1.49 eV. In the thermal evaporation, the source to substrate distance was 40 cm.…”
Section: Device Fabricationmentioning
confidence: 94%
See 2 more Smart Citations
“…However, we reported that the chemical precipitate is rich in elemental selenium, and hence, the composition is shifted toward Sb 2 S 1.5 Se 1.5 . 26 If E g of bulk Sb 2 S 3 (1.88 eV) and Sb 2 Se 3 (1.1 eV) and proportional variation of E g are valid for this solid solution, its value for this thin film would be 1.49 eV. In the thermal evaporation, the source to substrate distance was 40 cm.…”
Section: Device Fabricationmentioning
confidence: 94%
“…Thin film of Sb 2 (S x Se 1‐ x ) 3 was deposited onto the various electron buffer layers by vacuum thermal evaporation of a powder mixture containing 300 mg Sb 2 S 3 powder (Aldrich) and 300 mg Sb 2 Se 3 precipitate, which was obtained from a modified chemical solution reported in Pérez‐Martínez et al When the formula masses of Sb 2 S 3 (340 g) and Sb 2 Se 3 (480 g) are considered, and no relative loss of component elements occurs, the composition of the thin film would be Sb 2 S 1.75 Se 1.25 . However, we reported that the chemical precipitate is rich in elemental selenium, and hence, the composition is shifted toward Sb 2 S 1.5 Se 1.5 . If E g of bulk Sb 2 S 3 (1.88 eV) and Sb 2 Se 3 (1.1 eV) and proportional variation of E g are valid for this solid solution, its value for this thin film would be 1.49 eV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitate was recovered by filtration. It was rinsed with deionized water, dried and stored . The EDS of this precipitate showed Sb:S:Se proportion of 36:4:60.…”
Section: Methodsmentioning
confidence: 99%
“…The optical bandgap ( E g ) of such materials may be continuously varied between 1.1 eV (Sb 2 Se 3 ) and 1.88 eV (Sb 2 S 3 ), thereby offering in them E g of 1.3–1.6 eV recommended for successful solar cells . Solar cells have been prepared by thermal evaporation of powder samples of precipitates and/or commercial Sb 2 S 3 powder with solar‐to‐electric energy conversion efficiency ( η ) of up to 4.27% . Progress made in thin film solar cells of Sb 2 S x Se 3‐x produced by various modifications of thermal evaporation and/or postdeposition processing of the cell structures with η close to 7% has been reviewed in 2016–2017 .…”
Section: Introductionmentioning
confidence: 99%